ESP32-Based Sumo Robot Control System Using PlayStation 4 Controller with Semi-Autonomous Ultrasonic Features - Sidehabi, Sitti Wetenriajeng; Mubarak, Muhammad Muflih; Gani, Hamdan (ILKOM Jurnal Ilmiah, 2025)
This study presents the design and implementation of a sumo robot control system integrating an ESP32 Devkit V1 microcontroller with a wireless PlayStation 4 controller and semi-autonomous features based on the HC-SR04 ultrasonic sensor and MG-995 servo motor. The system addresses challenges in sumo robots, including communication stability and control precision. Hardware integration involved DC motors, an L298N driver, and a LiPo battery, while software development used the Arduino IDE with Bluetooth connectivity. Experimental testing demonstrated stable communication with a maximum range of 36 meters, an average controller connection time of 1.998 seconds, and 100% detection accuracy within a 10 cm radius. Push performance tests showed the robot could move loads up to 1655 g with standard tires and 3340 g with sponge tires. These results highlight the advantages of combining consumer-grade game controllers with advanced microcontrollers, offering improved precision, extended range, and intuitive user interaction for competitive robotics.